O olhar de um discente sobre seu futuro docente: uma trajetória auto formativa - Silva, Marcelo Pedroni da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The writings of this paper refer to several personal experiences as well as the various conflicts in the initial educational formation, where I'm reflecting about the formation intentions of this course. I do an analysis and a reflection of the pedagogical practices developed during graduation in institutional spaces, as well as the understanding of the complex context and teaching actions intrinsic to this, that are what constitute the structural dimensions which is where the formative process happens. This study is a narrative of initial formation as autobiographical. Memories and experiences are analyzed along with undergraduate education, exposing structural problems of course requiring a deeper analysis. In addition to analyse critically the institutional spaces of the (few) outreach programs, education and research that are the basis of the Brazilian University, the wellknown University quadripod. Under this perspective, the narrative brings the dichotomous design of the quadripod inside the University course, exposing the need to reflect on this fact, as it culminates in the formation of future teachers in physics. Nevertheless, the work seeks to raise awareness for the need for enhancement of teaching career at the University to address the teaching crisis which today proliferates in the educational institutions in Brazil, therefore it is necessary to the teachers to become aware of your profession and the vision as such. Only from this perspective one can discuss a proper teacher training, aiming at the integration of all activities, valuing all with the same importance

As escritas deste trabalho referem-se às experiências e vivências bem como os diversos conflitos da formação docente inicial, onde problematizo as intencionalidades formativas do curso de física, em especial a modalidade de licenciatura. A análise e a reflexão das práticas pedagógicas desenvolvidas durante a graduação nos espaços institucionais, bem como a compreensão do complexo contexto universitário e as ações docentes intrínsecas a este, são o que constituem as dimensões estruturais as quais o processo formativo se apoia. O estudo desenvolvido trata-se de uma narrativa de formação inicial de cunho autobiográfico. São analisadas memórias e experiências vividas ao longo da graduação com caráter formativo, expondo problemas estruturais do curso que necessitam de uma análise mais profunda. Além de analisar criticamente os espaços institucionais dos (poucos) programas de extensão, de ensino e pesquisa que constituem a base da universidade brasileira, o conhecido quadripé universitário. Sob esta perspectiva, a narrativa traz a concepção dicotomizada sobre o quadripé universitário dentro do curso, expondo a necessidade de refletir sobre este fato, pois culmina fortemente na formação dos futuros docentes em física. Não obstante, o trabalho busca conscientizar para a necessidade de valorização da carreira docente na universidade, pois para enfrentar a crise docente que hoje prolifera nas instituições escolares brasileiras, é necessário que os docentes se conscientizem de sua profissão e a concebam como tal. Somente a partir desta perspectiva pode-se discutir formação de professores de maneira apropriada, visando a integração entre todas as atividades docentes, valorizando-as igualmente
Keywords: Professores - Formação; Autobiografia; Aprendizagem experimental; Física - Estudo e ensino